Mitos Kecantikan Tubuh Wanita Pada Kakawin Smara Tantra - Adnyana, Putu Eka Sura; Yuliarmini, Ni Made (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
The concept of beauty attached to a woman's body does not only occur in the real world but also in literary works. Beauty myths form interpretations to women in the analyzed Smara Tantra kakawin. Beauty myths intimidate women in such a systematic and organized way. As long as women think that being beautiful according to the representation of society's glasses is an absolute necessity. Kakawin Smara Tantra, which is quite famous among Balinese people, only sees from the point of view of men the beautiful construction of women. Beauty myths created in kakawin Smara Tantra have shackled women so that women no longer respect themselves and only focus on physical form. Although the true beauty of women is not only radiated from the physical but must be balanced with beauty that comes from within (inner beauty).